Analysis of Factors Associated with Wus's Decision to Use an IUD in the Working Area of the Maja Public Health Center, Lebak Regency in 2024 - Indah Mulia Herwisdiane; Wayan Aryawati; Fitri Ekasari; Dhiny Easter Yanti (PROFESSIONAL HEALTH JOURNAL, 2025)
Birth control has become a global issue of great importance in maintaining a balance between population growth and available resources. One contraceptive method that is often used is the IUD. The prevalence of IUD/AKDR family planning acceptors in Indonesia is 3.8 % and in Banten 6.09%. The IUD has been a major focus of long-term contraceptive research because of its high effectiveness, reversibility, and potential additional health benefits. The aim of the research was to determine factors related to WUS's decision to use an IUD. This type of quantitative research with a cross sectional design. The population in the study, namely women of childbearing age in the Maja Health Center Working Area, numbered 9,394 and a sample of 369 people using the cluster random sampling technique . Data analysis used univariate, bivariate ( chi square), and multivariate ( multiple logistic regression). The results of bivariate analysis showed that there was no relationship between age (p=0.405), parity (p=0.837), and occupation (p= 0.875) with WUS's decision to use an IUD. Meanwhile, education (p=0.004), knowledge (p=0.000), attitude (p=0.038), husband's support (p=0.035), and support from health workers (p=0.029) affected WUS' decision to use an IUD. The factor most related to WUS's decision to use an IUD is knowledge with OR= 9.591. The conclusion from this research is that the dominant factor related to the decision to use an IUD is knowledge. WUS should actively seek information through trusted sources such as consulting with medical personnel at community health centers or reading accurate health literature.